Projection of Solar Energy Consumers as Renewable Energy in Indonesia - Avicenna, Fitria; Shobaruddin, Muhammad; Febriani, Nufian S (MediaTor (Jurnal Komunikasi), 2022)
In today's world, there is a shift from non-renewable to renewable energy sources. The potential of renewable energy, such as solar energy, has yet to be widely utilized, even though renewable energy has considerable potential, especially in Indonesia. For this study, researchers obtained data on solar panel consumers through the official contact list website for potential consumers of the Ministry of Energy and Mineral Resources. Researchers obtained data through online questionnaires distributed to 207 consumers of products related to the renewable energy. Researchers use this sample because they are consumers or users of the renewable energy in the form of solar panels. In data presentation, data in the form of responses received from online questionnaires can generally show the demographic characteristics of the respondents. This research aims to formulate an effective promotional strategy by identifying consumer characteristics.